The Influence of Family Support on Providing Complete Primary Immunizations - Ilhami Ilhami; Malik Afif (Universitas Airlangga, 2020)
Background: Primary immunizations is a series of vaccination given to babies before the age of one, and it can actively increase immunity to diseases such as Hepatitis B, Poliomyelitis, Tuberculosis, Diphtheria, Pertussis, Tetanus, Pneumonia, and Meningitis caused by Hemophilus influenza type B, and measles. Family support is one of the essential factors for the completeness of immunization because it will encourage parents to immunize their children. The social support theory was used here since it assumes that the source of support from families such as parents, siblings, children, relatives, and partners provides examples for individuals to perform or suggest a positive behavior. Objective: This study aimed to determine the effect of family support on the provision of complete primary immunization at the Sidotopo Health Center in Surabaya. Methods: This research used a descriptive-analytic method with a simple random sampling of 54 respondents with a degree of significance (α=0.05). Sample inclusion criteria include mothers who have children aged 12-24 months, have a health card (KMS), and live around the area of Sidotopo Health Centre. The exclusion criteria are those who were not willing to be respondents. Results: The effect of family support on immunization has a significant value of 0.015 (P Value <0.05) on emotional support, while the support of appreciation, instrumental support, and informative support are not substantial (P Value>0.05). Conclusion: Family support for complete primary immunizations includes emotional support, appreciation support, instrumental support, and informative support. Overall, emotional support has a direct influence on providing immunization. Therefore, appreciation support, instrumental support, and informative support did not significantly affect immunization.